Risk factors associated with treatment of hyperactive postoperative delirium in elderly patients following hip fracture surgery under regional anesthesia: a nationwide population-based study - Eun-Jin Ahn; Si Ra Bang (Brazilian Journal of Anesthesiology, 2022)
Background and objectives: Delirium is common but is frequently undetected by clinicians, despite the fact that it can be life-threatening. This study aimed to identify the incidence of delirium and the preoperative factors associated with perioperative use of drugs to treat hyperactive delirium in elderly patients who underwent hip fracture surgery under regional anesthesia. Methods: We retrospectively reviewed records of all patients ≥ 65 years of age who had undergone hip-fracture surgery under regional anesthesia, covered by the Korean National Health Insurance, between January 1, 2009 and December 31, 2015. A univariate and stepwise logistic regression model with the occurrence of hyperactive delirium as the dependent variable was used to identify the perioperative factors for this sample of patients. Results: Among the 70,696 patients who underwent hip fracture surgery, 58,972 patients who received regional anesthesia were included in our study; of these, perioperative use of drugs to treat hyperactive delirium was diagnosed in 8,680 (14.7%) patients. Performing stepwise logistic regression, preoperative variables found to be associated with delirium were: male sex, age ≥ 85 years, hospital type (medical center), ICU and ventilator care, the presence of a neurodegenerative disorder, uncomplicated diabetes mellitus, peptic ulcer disease, and previously diagnosed psychoses and/or depression (OR = 1.49 [1.42–1.58], 4.7 [4.15–5.37], 13.3 [7.57–23.8], 1.52 [1.43–1.60], 1.19 [1.01–1.40], 1.20 [1.14–1.27], 1.09 [1.04–1.14], 0.87 [0.96–0.00], 2.23 [1.48–3.37], and 1.38 [1.32–1.46], respectively). Conclusions: Postoperative hyperactive delirium may affect approximately 15% of elderly patients submitted to hip fracture repair under regional anesthesia. This study has identified multiple preoperative risk factors associated with postoperative hyperactive delirium and its pharmacological management strategies.